Construction of a high-density genetic map for hexaploid kiwifruit (Actinidia chinensis var. deliciosa) using genotyping by sequencing. Issue 7 (1st May 2021) - Popowski, Elizabeth; Thomson, Susan J; Knäbel, Mareike; Tahir, Jibran; Crowhurst, Ross N; Davy, Marcus; Foster, Toshi M; Schaffer, Robert J; Tustin, D Stuart; Allan, Andrew C; McCallum, John; Chagné, David
Abstract: Commercially grown kiwifruit (genus Actinidia ) are generally of two sub-species which have a base haploid genome of 29 chromosomes. The yellow-fleshed Actinidia chinensis var. chinensis, is either diploid ( 2n = 2x = 58) or tetraploid ( 2n = 4x = 116) and the green-fleshed cultivar A. chinensis var. deliciosa "Hayward, " is hexaploid ( 2n = 6x = 174). Advances in breeding green kiwifruit could be greatly sped up by the use of molecular resources for more efficient and faster selection, for example using marker-assisted selection (MAS). The key genetic marker that has been implemented for MAS in hexaploid kiwifruit is for gender testing. The limited marker-trait association has been reported for other polyploid kiwifruit for fruit and production traits. We have constructed a high-density linkage map for hexaploid green kiwifruit using genotyping-by-sequence (GBS). The linkage map obtained consists of 3686 and 3940 markers organized in 183 and 176 linkage groups for the female and male parents, respectively. Both parental linkage maps are co-linear with the A. chinensis "Red5" reference genome of kiwifruit. The linkage map was then used for quantitative trait locus (QTL) mapping, and successfully identified QTLs for king flower number, fruit number and weight, dry matter accumulation, and storage firmness. These are the first QTLs to be reported and discovered for complex traits in hexaploid kiwifruit.